Attentional Bias to High-Calorie Food in Binge Eaters With High Shape/Weight Concern - Seo, Chai Lee; Lee, Jang-Han (Frontiers in Psychiatry, 2021)
Individuals with high shape/weight concern (SWC) place disproportionate emphasis on shape and weight in evaluating their self-worth, making them more vulnerable to body-related cues. Binge eaters (BE), who are obsessed with devouring high-calorie foods, would show severe symptomatology especially when they have clinically high SWC. The present study attempted to elucidate how SWC influences bingeing based on attentional patterns toward high-calorie food cues. A total of 120 participants were selected and divided into four groups: (1) BE with high SWC, (2) BE with low SWC, (3) healthy controls (HC) with high SWC, and (4) HC with low SWC. BE and SWC status were respectively determined using the Eating Disorder Diagnostic Scale–DSM-5 and the Eating Disorder Examination-Questionnaire. All participants completed the same free-viewing task, measuring initial fixation latency and total fixation duration. BE with high SWC showed attentional bias toward high-calorie food cues in terms of significantly faster initial fixation latency and longer total fixation duration, whereas BE with low SWC and the HC groups did not show any differences. The results revealed that SWC level makes unique contributions to BE’s initial orienting bias toward and difficulty disengaging from high-calorie food cues. This may indicate that BE with high SWC merely worry about eating high-calorie food in a cognitive way, but not controlling actual bingeing behavior. The current study of attentional bias elucidated the role of SWC as a potential maintenance factor of concerning and bingeing in BE.